PARENTS’ COMPETENCE IN INFANT FLOATING FROM A SPECIALIST PERSPECTIVE - Kurmeļeva, Alina; Fernāte, Andra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Nowadays activities with the involvement of both children and parents are becoming increasingly popular. There are a variety of such activities, but in this study we focus on infant floating. It is very important how parents feel themselves in such type of lessons and how they are able to perform the exercises with their infants independently and orient themselves in a specific aquatic environment. Parents’ competences in infant floating on the whole are often characterised by their insufficient knowledge, skills and practical abilities in maintaining correct and proper behaviour in the aquatic environment. Therefore, the aim of our study is to explore and analyse the assessment of parents’ competences in infant floating. Based on the research results it would be possible to develop a more accurate model for the enhancement of the parents’ competences required for infant floating and put forward recommendations for improving parents' competences. An assessment survey of the parents' competences in infant floating was conducted from the beginning of September 2017 until the end of October. 33 swimming experts participated voluntarily in the assessment of parents’ competences in infant floating. The mean, standard deviation and mode was used to process the numerical data gathered from the responses. The content and statements put forward in the survey questionnaire regarding parents’ competences in infant floating were based on scientific concepts. The results of the survey of swimming experts indicate that all of the components proposed by the authors that influence parents’ competences in infant floating play a significant role. It could also be surely concluded that at present, the overall level of parental competence in infant floating in the opinion of experts is average. In general, all the surveyed swimming experts are of the opinion that parents should definitely supplement or acquire additional knowledge, skills and abilities in order to increase their level of competences in infant floating in order to be able to effectively apply these competences during independent lessons with their infants.